SWOT Analysis of School Readiness in Implementing Deep Learning at SDN Kendek, North Banggai District, Banggai Laut Regency - Asrianto Asrianto; Ansar Ansar; Zulystiawati ZulystiawatiZulystiawati (International Journal of Education, Culture, and Society, 2026)
The less-than-optimal readiness of elementary schools to implement a holistic deep learning approach—particularly in resource-limited settings—necessitates a comprehensive SWOT-based analysis to formulate strategies for strengthening institutional preparedness. This study aims to analyze (1) school readiness from internal factors related to the deep learning approach, (2) school readiness from external factors, and (3) strategies for improving school readiness in implementing deep learning at SDN Kendek. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, and subsequently analyzed using SWOT analysis. The findings show that, internally, teachers at SDN Kendek possess sufficient initial capital for implementing deep learning, including relatively high professional motivation to develop their competencies and keep pace with advances in learning technology; however, this internal readiness is not yet fully optimal due to persisting constraints. From an external perspective, the school has provided basic learning facilities that support technology use, such as laptops, LCD projectors, and internet access, but these resources remain inadequate to fully support the optimal implementation of deep learning. Based on the combined analysis of internal and external factors, improving school readiness for deep learning requires an integrated and sustainable strategy that not only focuses on developing teacher competencies, but also on strengthening school policies, providing adequate facilities, fostering collaboration with external partners, and enhancing communication with parents.